2021
DOI: 10.2147/opth.s309214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intraocular Lens Rotational Stability in a Multicenter Clinical Trial

Abstract: Purpose: To evaluate the postoperative rotational stability of two prototype intraocular lens (IOL) designs (subsequently termed version 1 and version 2). Patients and Methods: A prospective, multicenter, randomized, paired-eye, 6-month study evaluated the version 1 and version 2 IOLs. Results were compared with a control IOL (TECNIS ® toric 1-piece monofocal IOL) evaluated in a separate, similarly designed study. Participants aged ≥22 years and scheduled to undergo bilateral cataract extraction were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 14 publications
(43 reference statements)
2
27
0
1
Order By: Relevance
“…Rotation data from this study were compared with the POC data reported previously by Vukich et al, for a prototype non-toric monofocal IOL with fiducial axis marks (Prototype 2) with the same haptic design ( Figure 1 ). 14 In brief, that study was a prospective, randomized, multicenter paired-eye study using a similar study protocol and the same objective photographic method for measuring IOL rotation. A total of 99 eyes were implanted with the Prototype 2 IOL at one study site in Asia Pacific and two study sites in Latin America.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rotation data from this study were compared with the POC data reported previously by Vukich et al, for a prototype non-toric monofocal IOL with fiducial axis marks (Prototype 2) with the same haptic design ( Figure 1 ). 14 In brief, that study was a prospective, randomized, multicenter paired-eye study using a similar study protocol and the same objective photographic method for measuring IOL rotation. A total of 99 eyes were implanted with the Prototype 2 IOL at one study site in Asia Pacific and two study sites in Latin America.…”
Section: Methodsmentioning
confidence: 99%
“…15 It was designed to deliver improved rotational outcomes within the first week following implantation. The purpose of this study was to evaluate the reproducibility of postoperative IOL rotation of the TECNIS Toric II (Model ZCU) IOL compared to the prototype non-toric monofocal IOL with fiducial axis marks (Prototype 2), reported previously by Vukich et al 14 In addition, visual performance, residual astigmatism, and surgeon satisfaction with the TECNIS Toric II (Model ZCU) IOL were assessed. Insights into the appropriateness of comparing rotational stability results between subjects of different races and ethnicities were also gained.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Routine accuracy of axis placement is reported as within 5 0 of the intended axis. 69,70 Average of misalignment where the alignment axis is signed (positive for counter-clockwise from the intended axis and negative for clockwise) is close to zero with a mean absolute value of less than 5 0 . 71…”
Section: Axis Placement Accuracymentioning
confidence: 99%